The Impact of Technology Adoption, Monetary Policy, and Carbon Emissions an Green Finance in Asean-5 - Mohammad Adenan; Ciplis Gema Qori’ah; Amelia Delima Citra (Journal of Islamic Economics Perspectives, 2025)
The purpose of this research is to analyze the influence of AI adoption, monetary policy (represented by interest rates), and carbon emissions on green finance, specifically green bonds, in ASEAN-5 countries. The focus of the research is on mapping the trends and measuring the causal impact of Government AI Readiness Index, policy interest rate, and carbon emissions per capita on the value of outstanding green bonds in Indonesia, Malaysia, Thailand, Philippines, and Singapore. This research uses panel data covering quarterly periods from Q1 2019 to Q4 2024. The variables consist of Government AI Readiness Index (as a proxy of technology readiness), policy interest rates from IMF, carbon emissions per capita from Our World in Data, and green bond value data from the Asian Development Bank. The method applied is Panel Least Square (PLS). The results show that all three independent variables significantly affect the development of green bonds. First, higher AI readiness positively drives green bond issuance by improving efficiency, accuracy, and transparency in financing green projects. Second, lower policy interest rates have a positive effect on green bond growth, as cheaper borrowing costs make sustainable projects more financially feasible. Third, higher carbon emissions correlate positively with increased issuance of green bonds, as countries respond to environmental pressures and emission reduction demands.